The dynamics of low pay and unemployment in early 1990s Britain - Amanda Gosling; Paul Johnson; Julian McCrae; Gillian Paull (Institute for Fiscal Studies (IFS), 1997)
This report shows the extent to which low pay and unemployment are related, the effects of periods out of work on future earnings and the degree to which low pay is a persistent phenomenon. Importantly it demonstrates the way in which a minimum wage might affect a much higher proportion of the population than is generally appreciated because of the way in which people move in and out of low paid work. A chapter of the report is also given over to the effects of work experience and job tenure on pay levels.
Keywords: 330